Magnetic Resonance Spectroscopy Studies of Glutamate-Related Abnormalities in Mood Disorders - Yüksel, Cagri (2010)
In mood disorders there is growing evidence for glutamatergic abnormalities derived from peripheral measures of glutamatergic metabolites in patients, postmortem studies on glutamate related markers, and animal studies on the mechanism of action of available treatments. Magnetic resonance spectroscopy (MRS) has the potential to corroborate and extend these findings with the advantage of in vivo assessment of glutamate-related metabolites in different disease states, in response to treatment, and in relation with functional imaging data. In this article we first review the biological significance of glutamate, glutamine, and Glx (composed mainly of glutamate and glutamine). Next we review the MRS literature in mood disorders examining these glutamate-related metabolites. Here, we find a highly consistent pattern of Glx level reductions in major depressive disorder and elevations in bipolar disorder. In addition, studies of depression regardless of diagnosis provide suggestive evidence for reduced glutamine/glutamate ratio, and in mania for elevated glutamine/glutamate ratio. These patterns suggest that the glutamate-related metabolite pool (not all of it necessarily relevant to neurotransmission) is constricted in major depressive disorder and expanded in bipolar disorder. Depressive and manic episodes may be characterized by modulation of the glutamine/glutamate ratio in opposite directions, possibly suggesting reduced vs. elevated glutamate conversion to glutamine by glial cells, respectively. We discuss the implications of these results for the pathophysiology of mood disorders, and suggest future directions for MRS studies.